-
Notifications
You must be signed in to change notification settings - Fork 2
/
Copy pathic-derivations.tex
417 lines (390 loc) · 16.1 KB
/
ic-derivations.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
\chapter{Derivations in Arithmetic Theories}
When we showed that all general recursive functions are representable
in~$\Th{Q}$, and in the proofs of the incompleteness theorems, we
claimed that various things are provable in $\Th{Q}$ and~$\Th{PA}$. The
proofs of these claims, however, just gave the arguments informally
without exhibiting actual derivations in natural deduction. We provide
some of these derivations in this capter.
For instance, in \olref[inc][req][bre]{lem:q-proves-add} we proved
that, for all $n$ and $m \in \Nat$, $\Th{Q} \Proves (\num{n} +
\num{m}) = \num{n+m}$. We did this by induction on $m$.
\begin{proof}[Proof of {\olref[inc][req][bre]{lem:q-proves-add}}]
Base case: $m = 0$. Then what has to be proved is that, for all $n$,
$\Th{Q} \Proves \num{n} + \num{0} = \num{n+0}$. Since $\num{0}$ is
just $\Obj 0$ and $\num{n+0}$ is $\num{n}$, this amounts to showing
that $\Th{Q} \Proves (\num{n} + \Obj 0) = \num{n}$. The derivation
\begin{prooftree}
\AxiomC{$\lforall[x][(x + \Obj 0) = x]$}
\RightLabel{\Elim\lforall}
\UnaryInfC{$(\num{n} + \Obj 0) = \num{n}$}
\end{prooftree}
is a natural deduction derivation of $(\num{n} + \Obj 0) = \num{n}$
with one undischarged assumption, and that undischarged assumption is
an axiom of~$\Th{Q}$.
Inductive step: Suppose that, for any $n$, $\Th{Q} \Proves (\num{n} +
\num{m}) = \num{n+m}$ (say, by a derivation $\delta_{n,m}$). We have
to show that also $\Th{Q} \Proves (\num{n} + \num{m+1}) =
\num{n+m+1}$. Note that $\num{m+1} \ident \num{m}'$, and that
$\num{n+m+1} \ident \num{n+m}'$. So we are looking for a derivation of
$(\num{n} + \num{m}') = \num{n+m}'$ from the axioms of~$\Th{Q}$. Our
derivation may use the derivation $\delta_{n,m}$ which exists by inductive
hypothesis.
\begin{prooftree}
\AxiomC{}
\RightLabel{$\delta_{n,m}$}
\DeduceC{$(\num{n} + \num{m}) = \num{n+m}$}
\AxiomC{$\lforall[x][\lforall[y][(x+y') = (x+y)']]$}
\RightLabel{\Elim\lforall}
\UnaryInfC{$\lforall[y][(\num{n}+y') = (\num{n}+y)']$}
\RightLabel{\Elim\lforall}
\UnaryInfC{$(\num{n}+\num{m}') = (\num{n}+\num{m})'$}
\RightLabel{\Elim=}
\BinaryInfC{$(\num{n}+\num{m}') = \num{n+m}'$}
\end{prooftree}
In the last $\Elim=$ inference, we replace the subterm $\num{n} +
\num{m}$ of the right side $(\num{n} + \num{m})'$ of the right premise
by the term $\num{n+m}$.
\end{proof}
In \olref[inc][req][min]{lem:less-zero}, we showed that $\Th{Q} \Proves
\lforall[x][\lnot x < \Obj 0]$. What does an actual derivation look like?
\begin{proof}[Proof of {\olref[inc][req][min]{lem:less-zero}}]
To prove a universal claim like this, we use $\Intro\lforall$, which
requires a derivation of $\lnot a < \Obj 0$. Looking at axiom $!Q_8$,
this means proving $\lnot \exists z (z' + a) = \Obj 0$. Specifically,
if we had a proof of the latter, $!Q_8$ would allow us to prove the
former (recall that $A \liff B$ is short for $(A \lif B) \land (B \lif
A)$.
\begin{prooftree}\footnotesize
\AxiomC{$\lnot\lexists[z][(z' + a) = \Obj 0]$}
\AxiomC{$\lforall[x][\lforall[y][(x < y \liff \lexists[z][(z' + x) = y])]]$}
\RightLabel{\Elim\lforall}
\UnaryInfC{$\lforall[y][(a < y \liff \lexists[z][(z' + a) = y])]$}
\RightLabel{\Elim\lforall}
\UnaryInfC{$a < \Obj 0 \liff \lexists[z][(z' + a) = \Obj 0]$}
\RightLabel{\Elim\land}
\UnaryInfC{$a < \Obj 0 \lif \lexists[z][(z' + a) = \Obj 0]$}
\AxiomC{$\Discharge{a < \Obj 0}{1}$}
\RightLabel{\Elim\lif}
\BinaryInfC{$\lexists[z][(z' + a) = \Obj 0]$}
\RightLabel{\Elim\lnot}
\insertBetweenHyps{\hskip -3em}
\BinaryInfC{$\lfalse$}
\DischargeRule{\Intro\lnot}{1}
\UnaryInfC{$\lnot a<\Obj 0$}
\end{prooftree}
This is a derivation of $\lnot a<\Obj 0$ from $\lnot\lexists[z][(z' +
a) = \Obj 0]$ (and~$!Q_8$); let's call it~$\delta_1$.
Now how do we prove $\lnot\lexists[z][(z' + a) = \Obj 0]$ from the
axioms of~$\Th{Q}$? To prove a negated claim like this, we'd need a
derivation of the form
\begin{prooftree}
\AxiomC{$\Discharge{\lexists[z][(z' + a) = \Obj 0]}{2}$}
\DeduceC{$\lfalse$}
\DischargeRule{\Intro\lnot}{2}
\UnaryInfC{$\lnot\lexists[z][(z' + a) = \Obj 0]$}
\end{prooftree}
To get a contradiction from an existential claim, we introduce a
constant~$b$ for the existentially quantified variable~$z$ and use
\Elim\lexists:
\begin{prooftree}
\AxiomC{$\Discharge{\lexists[z][(z' + a) = \Obj 0]}{2}$}
\AxiomC{$\Discharge{(b'+a) = \Obj 0}{3}$}
\RightLabel{$\delta_2$}
\DeduceC{$\lfalse$}
\DischargeRule{\Elim\exists}{3}
\BinaryInfC{$\lfalse$}
\DischargeRule{\Intro\lnot}{2}
\UnaryInfC{$\lnot\lexists[z][(z' + a) = \Obj 0]$}
\end{prooftree}
Now the task is to fill in $\delta_2$, i.e., prove $\lfalse$ from
$(b'+a) = \Obj 0$ and the axioms of~$\Th{Q}$. $Q_2$ says that $\Obj 0$
can't be the successor of some number, so one way of doing that would
be to show that $(b' + a)$ is equal to the successor of some number.
Since that expression itself is a sum, the axioms for addition must
come into play. If $\eq[a][\Obj 0]$, $Q_5$ would tell us that $\eq[(b'
+ a)][b']$, i.e., $b' + a$ is the successor of some number, namely
of~$b$. On the other hand, if $\eq[a][c']$ for some $c$, then
$\eq[(b'+a)][(b'+c')]$ by \Elim\eq, and $\eq[(b'+c')][(b'+c)']$
by~$Q_6$. So again, $b'+a$ is the successor of a number---in this
case, $b'+c$. So the strategy is to divide the task into these two
cases. We also have to verify that $\Th{Q}$ proves that one of these
cases holds, i.e., $\Th{Q} \Proves a = 0 \lor \lexists[y][(a = y')]$,
but this follows directly from $Q_3$ by \Elim\lforall. Here are the
two cases:
Case 1: Prove $\lfalse$ from $\eq[a][\Obj 0]$ and $\eq[(b'+a)][\Obj
0]$ (and axioms $Q_2$, $Q_5$):
\begin{prooftree}\footnotesize
\AxiomC{$\lforall[x][\lnot \Obj 0 = x']$}
\RightLabel{\Elim\lforall}
\UnaryInfC{$\lnot \Obj 0 = b'$}
\AxiomC{$\lforall[x][(x+\Obj 0) = x]$}
\RightLabel{\Elim\lforall}
\UnaryInfC{$(b' + \Obj 0) = b'$}
\AxiomC{$a = \Obj 0$}
\AxiomC{$(b'+a) = \Obj 0$}
\RightLabel{\Elim=}
\BinaryInfC{$(b' + \Obj 0) = \Obj 0$}
\doubleLine
\UnaryInfC{$\Obj 0 = (b' + \Obj 0)$}
\insertBetweenHyps{\hskip -.5em}
\RightLabel{\Elim=}
\BinaryInfC{$\Obj 0 = b'$}
\RightLabel{\Elim\lnot}
\BinaryInfC{$\lfalse$}
\end{prooftree}
Call this derivation~$\delta_3$. (We've abbreviated the derivation of
$\Obj 0 = (b' + \Obj 0)$ from $(b' + \Obj 0) = \Obj 0$ by a double
inference line.)
Case 2: Prove $\lfalse$ from $\lexists[y][a = y']$ and
$\eq[(b'+a)][\Obj 0]$ (and axioms $Q_2$, $Q_6$). We first show how to
derive $\lfalse$ from $\eq[a][c']$ and $\eq[(b'+a)][\Obj 0]$.
\begin{prooftree}\footnotesize
\AxiomC{$\lforall[x][\lnot \Obj 0 = x']$}
\RightLabel{\Elim\lforall}
\UnaryInfC{$\lnot \Obj 0 = (b'+c)'$}
\AxiomC{$a = c'$}
\AxiomC{$(b'+a) = \Obj 0$}
\RightLabel{\Elim=}
\insertBetweenHyps{\hskip -.3em}
\BinaryInfC{$\Obj (b'+c') = \Obj 0$}
\AxiomC{$\lforall[x][\lforall[y][(x+y') = (x+y)']]$}
\RightLabel{\Elim\lforall}
\UnaryInfC{$\lforall[y][(b'+y') = (b'+y)']$}
\RightLabel{\Elim\lforall}
\UnaryInfC{$(b' + c') = (b'+c)'$}
\RightLabel{\Elim=}
\insertBetweenHyps{\hskip .5em}
\BinaryInfC{$\Obj 0 = (b' + c)'$}
\RightLabel{\Elim\lnot}
\insertBetweenHyps{\hskip -.5em}
\BinaryInfC{$\lfalse$}
\end{prooftree}
Call this $\delta_4$. We get the required derivation $\delta_5$ by
applying $\Elim\lexists$ and discharging the assumption $\eq[a][c']$:
\begin{prooftree}
\AxiomC{$\lexists[y][a=y']$}
\AxiomC{$\Discharge{a = c'}{6} \quad \eq[(b'+a)][\Obj 0]$}
\RightLabel{$\delta_4$}
\DeduceC{$\lfalse$}
\DischargeRule{\Elim\exists}{6}
\BinaryInfC{$\lfalse$}
\end{prooftree}
Putting everything together, the full proof looks like this:
\begin{prooftree}\footnotesize
\AxiomC{$\Discharge{\lexists[z][(z' + a) = \Obj 0]}{2}$}
\AxiomC{$\begin{gathered}
\lforall[x][(x = 0 \lor {}]\\
\lexists[y][(a = y')])
\end{gathered}$}
\RightLabel{\Elim\lforall}
\UnaryInfC{$\begin{gathered}a = 0 \lor {}\\
\lexists[y][(a = y')]
\end{gathered}$}
\AxiomC{$\begin{gathered}[b]
\Discharge{a = \Obj 0}{7} \\
\Discharge{(b'+a) = \Obj 0}{3}
\end{gathered}$}
\RightLabel{$\delta_3$}
\DeduceC{$\lfalse$}
\AxiomC{$\begin{gathered}[b]
\Discharge{\lexists[y][a=y']}{7} \\
\Discharge{(b'+a) = \Obj 0}{3}
\end{gathered}$\quad}
\RightLabel{$\delta_5$}
\DeduceC{$\lfalse$}
\DischargeRule{\Elim\lor}{7}
\insertBetweenHyps{\hskip -.5em}
\TrinaryInfC{$\lfalse$}
\RightSubproofLabel{$\delta_2$}
\DischargeRule{\Elim\exists}{3}
\BinaryInfC{$\lfalse$}
\DischargeRule{\Intro\lnot}{2}
\UnaryInfC{$\lnot\lexists[z][(z' + a) = \Obj 0]$}
\RightLabel{$\delta_1$}
\DeduceC{$\lnot a<\Obj 0$}
\RightLabel{\Intro\lforall}
\UnaryInfC{$\lforall[x][\lnot x < \Obj 0]$}
\end{prooftree}
\end{proof}
In the proof of \olref[inc][inp][ros]{thm:rosser}, we defined
$\ORProv(y)$ as \[\lexists[x][(\OPrf(x, y) \land \lforall[z][(z < x
\lif \lnot \ORefut(z, y))])].\] $\OPrf(x,y)$ is the formula
representing the proof relation of~$\Th{T}$ (a consistent,
axiomatizable extension of~$\Th{Q}$) in $\Th{Q}$, and $\ORefut(z, y)$
is the formula representing the refutation relation. That means that
if $n$ is the G\"odel number of a proof of~$!A$, then $\Th{Q} \Proves
\OPrf(\num{n}, \gn{!A})$, and otherwise $\Th{Q} \Proves
\lnot\OPrf(\num{n}, \gn{!A})$. Similarly, if $n$ is the G\"odel number
of a proof of $\lnot !A$, then $\Th{Q} \Proves \ORefut(\num{n},
\gn{!A})$, and otherwise $\Th{Q} \Proves \lnot\ORefut(\num{n},
\gn{!A})$. We use the Diagonal Lemma to find a sentence $!R$ such that
$\Th{Q} \Proves !R \liff \lnot \ORProv(\gn{!R})$. Rosser's Theorem
states that $\Th{T} \Proves/ !R$ and $\Th{T} \Proves/ \lnot !R$. Both
claims were proved indirectly: we show that if $\Th{T} \Proves !R$,
$\Th{T}$ is inconsistent, i.e., $\Th{T} \Proves \lfalse$, and the same
if $\Th{T} \Proves \lnot !R$.
\begin{proof}[Proof of {\olref[inc][inp][ros]{thm:rosser}}]
First we prove something things about~$<$. By
\olref[inc][req][min]{lem:less-nsucc}, we know that $\Th{Q} \Proves
\lforall[x][(x < \num {n+1} \lif (\eq[x][\Obj 0] \lor \dots \lor
\eq[x][\num n]))]$ for every~$n$. So of course also (if $n>1$),
$\Th{Q} \Proves \lforall[x][(x < \num {n} \lif (\eq[x][\Obj 0] \lor
\dots \lor \eq[x][\num{n-1}]))]$. We can use this to derive
$\eq[a][\Obj 0] \lor \dots \lor \eq[a][\num{n-1}]$ from $a < \num{n}$:
\begin{prooftree}
\AxiomC{$a < \num{n}$}
\AxiomC{}
\DeduceC{$\lforall[x][(x < \num{n} \lif (x = \num{0} \lor
\dots \lor x = \num{n-1}))]$}
\RightLabel{\Elim\forall}
\UnaryInfC{$a < \num{n} \lif (a = \num{0} \lor
\dots \lor a = \num{n-1})$}
\RightLabel{\Elim\lif}
\BinaryInfC{$a = \num{0} \lor \dots \lor a = \num{n-1}$}
\end{prooftree}
Let's call this derivation $\lambda_1$.
Now, to show that $\Th{T} \Proves/ !R$, we assume that $\Th{T}
\Proves !R$ (with a derivation~$\delta$) and show that $\Th{T}$ then
would be inconsistent. Let $n$ be the G\"odel number
of~$\delta$. Since $\OPrf$ represents the proof relation in~$\Th{Q}$,
there is a derivation~$\delta_1$ of $\OPrf(\num{n},
\gn{!R})$. Furthermore, no $k < n$ is the G\"odel number of a
refutation of~$!R$ since $\Th{T}$ is assumed to be consistent, so for
each $k < n$, $\Th{Q} \Proves \lnot \ORefut(\num{k}, \gn{!R})$; let
$\rho_k$ be the corresponding derivation. We get a derivation of
$\ORProv(\gn{!R})$:
\begin{prooftree}\footnotesize
\AxiomC{}
\RightLabel{$\delta_1$}
\DeduceC{$\OPrf(\num{n}, \gn{!R})$}
\AxiomC{$\Discharge{a < \num{n}}{1}$}
\RightLabel{$\lambda_1$}
\DeduceC{$\begin{gathered}[b]
a= \num{0} \lor \dots {} \\
{} \lor a = \num{n-1}
\end{gathered}$}
\AxiomC{$\dots$}
\AxiomC{$\Discharge{a=\num{k}}{2}$}
\AxiomC{}
\RightLabel{$\rho_k$}
\DeduceC{$\lnot \ORefut(\num{k}, \gn{!R})$}
\RightLabel{\Elim=}
\BinaryInfC{$\lnot \ORefut(a, \gn{!R})$}
\AxiomC{$\dots$}
\DischargeRule{$\Elim\lor^*$}{2}
\doubleLine
\insertBetweenHyps{\hskip -1pt}
\QuaternaryInfC{$\lnot \ORefut(a, \gn{!R})$}
\DischargeRule{\Intro\lif}{1}
\UnaryInfC{$a < \num{n} \lif \lnot \ORefut(a, \gn{!R})$}
\RightLabel{\Intro\lforall}
\UnaryInfC{$\lforall[z][(z < \num{n} \lif \lnot \ORefut(z, \gn{!R}))]$}
\insertBetweenHyps{\hskip -5pt}
\RightLabel{\Intro\land}
\BinaryInfC{$\OPrf(\num{n}, \gn{!R}) \land \lforall[z][(z < \num{n} \lif \lnot \ORefut(\num{z}, \gn{!R}))]$}
\RightLabel{\Intro\lexists}
\UnaryInfC{$\lexists[x][(\OPrf(x, \gn{!R}) \land \lforall[z][(z < x \lif \lnot \ORefut(z, \gn{!R}))])]$}
\end{prooftree}
(We abbreviate multiple applications of $\Elim\lor$ by $\Elim\lor^*$
above.) We've shown that if $\Th{T} \Proves !R$ there would be a
derivation of~$\ORProv(\gn{!R})$. Then, since $\Th{T} \Proves R \liff
\lnot \ORProv(\gn{!R})$, also $\Th{T} \Proves \ORProv(\gn{!R}) \lif
\lnot R$, we'd have $\Th{T} \Proves \lnot !R$ and $\Th{T}$ would be
inconsistent.
Now let's show that $\Th{T} \Proves/ \lnot !R$. Again, suppose it
did. Then there is a derivation $\rho$ of $\lnot !R$ with G\"odel
number $m$---a refutation of~$!R$---and so $\Th{Q} \Proves
\ORefut(\num{m}, \gn{!R})$ by a derivation~$\rho_1$. Since we assume
$\Th{T}$ is consistent, $\Th{T} \Proves/ !R$. So for all $k$, $k$ is
not a G\"odel number of a derivation of~$!R$, and hence $\Th{Q} \Proves \lnot
\OPrf(\num{k}, \gn{!R})$ by a derivation~$\pi_k$. So we have:
\begin{prooftree}\footnotesize
\AxiomC{}
\RightLabel{$\lambda_2$}
\DeduceC{$\begin{gathered}[b] a = \num{0} \lor \dots \lor\\
a = \num{m} \lor \num{m} < a\end{gathered}$}
\AxiomC{$\dots$}
\AxiomC{$\begin{gathered}\Discharge{\OPrf(a, \gn{!R})}{1}\\
\Discharge{a = \num{k}}{2}\end{gathered}$}
\RightLabel{$\pi_k'$}
\DeduceC{$\lfalse$}
\RightLabel{$\lfalse_I$}
\UnaryInfC{$\num{m}<a$}
\AxiomC{$\dots$}
\AxiomC{$\Discharge{\num{m} < a}{2}$}
\DischargeRule{$\Elim\lor^*$}{2}
\insertBetweenHyps{\hspace{-.1em}}
\doubleLine
\QuinaryInfC{$\num{m} < a$}
\AxiomC{}
\RightLabel{$\rho_1$}
\DeduceC{$\ORefut(\num{m}, \gn{!R})$}
\RightLabel{\Intro\land}
\insertBetweenHyps{\hspace{-.1em}}
\BinaryInfC{$\num{m}
< a \land \ORefut(\num{m}, \gn{!R})$}
\RightLabel{\Intro\exists}
\UnaryInfC{$\exists z(z
< a \land \ORefut(z, \gn{!R}))$}
\DischargeRule{\Intro\lif}{1}
\UnaryInfC{$\OPrf(a, \gn{!R}) \lif \exists z(z
< a \land \ORefut(z, \gn{!R}))$}
\RightLabel{\Intro\forall}
\UnaryInfC{$\forall x(\OPrf(x, \gn{!R}) \lif \exists z(z
< x \land \ORefut(z, \gn{!R})))$}
\DeduceC{$\lnot\exists x(\OPrf(x, \gn{!R}) \land \forall z(z
< x \lif \lnot \ORefut(z, \gn{!R})))$}
\end{prooftree}
where $\pi_k'$ is the derivation
\begin{prooftree}
\AxiomC{}
\RightLabel{$\pi_k$}
\DeduceC{$\lnot \OPrf(\num{k}, \gn{!R})$}
\AxiomC{$a = \num{k}$}
\AxiomC{$\OPrf(a, \gn{!R})$}
\RightLabel{\Elim=}
\BinaryInfC{$\OPrf(\num{k}, \gn{!R})$}
\RightLabel{\Elim\lnot}
\BinaryInfC{$\lfalse$}
\end{prooftree}
and $\lambda_2$ is
\begin{prooftree}\footnotesize
\AxiomC{}
\RightLabel{$\lambda_3$}
\DeduceC{$\begin{gathered}[b](a < \num{m} \lor {}\\a = \num{m}) \lor {}\\ \num{m} < a\end{gathered}$}
\AxiomC{$\Discharge{a < \num{m}}{3}$}
\RightLabel{$\lambda_1$}
\DeduceC{$\begin{gathered}[b]a = \num{0} \lor \dots \lor {}\\
a = \num{m-1}\end{gathered}$}
%\RightLabel{\Intro\lor}
\doubleLine
\UnaryInfC{$\begin{gathered}[b]
a = \num{0} \lor \dots \lor \\
a = \num{m} \lor \num{m} < a
\end{gathered}$}
\AxiomC{$\Discharge{a = \num{m}}{3}$}
%\RightLabel{\Intro\lor}
\doubleLine
\UnaryInfC{$\begin{gathered}[b]
a = \num{0} \lor \dots \lor \\
a = \num{m} \lor \num{m} < a
\end{gathered}$}
\AxiomC{$\Discharge{\num{m} < a}{3}$}
\doubleLine
\RightLabel{$\Intro\lor^*$}
\UnaryInfC{$\begin{gathered}[b]
a = \num{0} \lor \dots \lor \\
a = \num{m} \lor \num{m} < a
\end{gathered}$}
%\insertBetweenHyps{\hskip 5pt}
\doubleLine
\DischargeRule{$\Elim\lor^2$}{3}
\QuaternaryInfC{$a = \num{0} \lor \dots \lor a = \num{m} \lor \num{m} < a$}
\end{prooftree}
(The derivation $\lambda_3$ exists by
\olref[inc][req][min]{lem:trichotomy}. We abbreviate repeated use of
$\Intro\lor$ by $\Intro\lor^*$ and the double use of $\Elim\lor$ to
derive $a = \num{0} \lor \dots \lor a = \num{m} \lor \num{m} < a$ from
$(a < \num{m} \lor a = \num{m}) \lor \num{m} < a$ as $\Elim\lor^2$.)
\end{proof}
\OLEndChapterHook